Towards a Communication Theology - Tharaniyil, Biju (Journal of Dharma, 2004)
This book is a collection of papers attempting to awaken the sleeping Catholic conscience to the challenges of the "information super highway." Besides the introductory essays, the whole work is divided into two parts: i) Communication Theology: Method, and ii) Communication Theology: Practice.